THE ROLE OF IMPROVING ENTREPRENEUR COMPETENCY, INNOVATION AND USE OF SOCIAL MEDIA IN THE SUSTAINABILITY OF MSMES IN BANYUMAS DISTRICT - Kholifaturrohmah, Ramita; Widiastuti, Ekaningtyas; Mulasiwi, Cut Misni; Wakhidati, Yusmi Nur (Transpublika Publisher, 2023)
Every company must be able to compete in facing the challenges of globalization. Increasing business actors' competence (knowledge, skills, abilities) and innovative products is a primary concern to win the competition and achieve business sustainability. Mainly if MSMEs can utilize social media strategically in developing their business. This research focuses on MSMEs in the Banyumas Regency area to examine increasing entrepreneurial competence, innovation and the use of social media towards achieving sustainable MSMEs. The sample obtained was 51 MSME respondents. The analysis method uses multiple regression. Based on the results of the analysis, it shows that knowledge and social media have a positive and significant effect on the sustainability of MSMEs. In contrast, skills, abilities and innovation do not affect the sustainability of MSMEs. Based on the research results, the implication is that MSME actors can pay more attention to skills, abilities, and innovation, which must continue to be improved to produce better patterns, motifs and product quality and will maintain the company's existence and compete sustainably.